Innovation, advertising, personal selling, and sustainability in the industries massively benefited from major public health emergencies: paradoxical evidence from China - Xie, Guangying; Zhang, Cancan; Fang, Qianqian; Tang, Xiaole; Zhang, Yani (Frontiers in Public Health, 2023)
Background While major public health emergencies have severe socio-economic impacts, they may also present many opportunities for certain industries. For these industries that have benefited significantly (e.g., China’ s healthcare industry), the traditional emphasis on improving business performance through increased investment in innovation, marketing and sustainability may face contextual applicability challenges. Methods We used the data of healthcare industry in China during Covid-19 and the methods of hierarchical regression, moderating effect test to analyze the impact of innovation, advertising, personal selling, and sustainability on healthcare firms’ profitability. Three kinds of robust test including increasing the measurement range of variables, changing the data source and parameter estimation method, and Quantile regression are used. Results This paper finds that innovation, advertising, and environmental sustainability have significant negative impacts on profitability, while personal selling, social sustainability, and governance sustainability have significant positive impacts on profitability in the industries massively benefited from major public health emergencies. Besides, social sustainability can significantly moderate the relationship between innovation and profitability. Conclusion On one hand, for companies in industries that have benefited greatly from major public health emergencies, a shift in resource allocation from innovation, advertising, and environmental sustainability to personal selling, social sustainability, and governance sustainability may be more conducive to improving their profitability. On the other hand, for public health regulatory authorities, it is necessary to strengthen the supervision of sales representatives of health care enterprises, hospitals, public health organizations, etc., and appropriately subsidize the innovation of enterprises to enhance their innovation motivation.